New Insights Into the Role of Follicle-Stimulating Hormone in Sex Differentiation of the Protogynous Orange-Spotted Grouper, Epinephelus coioides - Huang, Minwei; Chen, Jiaxing; Liu, Yun; Chen, Huimin; Yu, Zeshu; Ye, Zhifeng; Peng, Cheng; Xiao, Ling; Zhao, Mi; Li, Shuisheng; Lin, Haoran; Zhang, Yong (Frontiers in Endocrinology, 2019)
Follicle-stimulating hormone (FSH) signalling is considered to be essential for early gametogenesis in teleosts, but its functional roles during sex differentiation are largely unknown. In this study, we investigated the effects of long-term and short-term FSH injection on sex differentiation in the protogynous orange-spotted grouper (Epinephelus coioides). Long-term FSH treatment initially promoted the formation of ovaries but subsequently induced a male fate. The expression of female pathway genes was initially increased but then decreased, whereas the expression of male pathway genes was up-regulated only during long-term FSH treatment. The genes related to the synthesis of sex steroid hormones, as well as serum 11-ketotestosterone and estradiol, were also up-regulated during long-term FSH treatment. Short-term FSH treatment activated genes in the female pathway (especially cyp19a1a) at low doses but caused inhibition at high doses. Genes in the male pathway were up-regulated by high concentrations of FSH over the short term. Finally, we found that low, but not high, concentrations of FSH treatment activated cyp19a1a promoter activities in human embryonic kidney (HEK) 293 cells. Overall, our data suggested that FSH may induce ovarian differentiation or a change to a male sex fate in the protogynous orange-spotted grouper, and that these processes occurred in an FSH concentration-dependent manner.